Emigration and elections: The role of emigrants' missing votes - Yvonne Giesing; Felicitas Schikora; Geisi Shima (EconPol Forum, 2023)
Emigrants typically differ from the origin population in terms of age, education, and political prefe-rences. Emigrants are also voting less in their country of origin even if they have the right to vote. As emigrants are not voting in their country of origin, their votes are missing. This can influence elections if emigration is large, and elections are tight. Policies facilitating voting for the diaspora can ensure better representation
Keywords: 330